The mportance of considering Custom (Urf/Adat) in issuing Fatwa (Ifta') in Ibn Abidin's Sharh 'Uqud Rasm al-Mufti = Kepentingan menimbang Adat (ÑURF/ÑÓDAT) dalam mengeluarkan Fatwa (IFTĀ’) Dalam Ibn ÑÓbidin’s SharÍ ÑUqËd Rasm al-Mufti - Ali, Mohammed Farid (IIUM Press, International Islamic University Malaysia, 2017)
It is necessary for a Mufti to know the custom ('urf/'adat) of his people and place. Non awareness of custom will result in mufti’s fatwa not being at par with the problems and demands of the developing societies. This paper emphasizes the important role custom plays in shari'ah, essentiality of its knowledge for the jurists/muftis, and its significance in issuing fatwa (al-ifta’), while referring to the translation of Ibn 'Abidin’s Sharh 'Uqud Rasm al-Mufti (Commentary on Mufti’s Manual). The paper finds that there is no way out for a mufti to issue a fatwa, while ignoring the custom of his time. Fatwa is a tool for the evolution of shari'ah in dealing with the evolving worldly affairs, and guarantees the most suitable solution in changing circumstances, provided that the custom of the people are taken into consideration.